The Effect Of Scramble Game By Using Quiziz Application On Students Vocabulary Mastery At SMP Gajah Mada Medan - Cici Suzana Saragih; Sahlan Tampubolon; Harpen Silitonga (Universitas Pahlawan Tuanku Tambusai, 2023)
Vocabulary as the basic to speak with other people is very important. By having many vocabularies, people can communicate with other people fluently. Scramble game by using Quiziz application was used to increase student’s vocabulary achievement. The objective of this study was to find out the effect of scramble game by using Quiziz application on student’s vocabulary mastery at SMP Gajah Mada Medan.This study was carried out by Experimental quantitative research. The object of this study was the nine grade students at SMP Gajah Mada Medan. It consisted of 40 students which included two groups, the experimental and control group. Scramble game was used to teach the experimental group while conventional strategy was used to teach control group. The instrument of data collection was reorder the words, drag and drop vocabulary test with 20 items. The mean of the student’s scores for the pre-test in the experimental group was 62,555 and the mean of the the post-test in the experimental group was 80,2 while the mean for the pre-test in the control group was 61,45, and the mean for the post-test was 73,45. The calculation revealed that the reliability was 5,479. The T-test formula was used to analyze the data. The calculation revealed that t-observed (5,479) was greater than t-table (2,026) at the level of significance (a) 0,05 and with a degree of freedom (df) of 38. It means that Scramble Game by using Quiziz Application had a significant effect on students' vocabulary mastery. So Ha was accepted.